The Quality of Connections: Deliberative Reciprocity and Inclusive Listening as Antidote to Destructive Polarization Online - Katharina Esau (Social Media + Society)
Conflict and disagreement are integral to healthy democracies, but the extreme polarization observed on many social media platforms poses a serious risk to the core functions of public communication. This theoretical article draws on the concept of connective democracy, further theorizing it to bridge the gap between empirical online deliberation and polarization research. It introduces and refines the concept of destructive polarization and its symptoms—manifested in user-generated content on social media platforms—and applies connective democracy theory to examine these symptoms’ underlying causes. The framework shifts from the dominant focus on the quality of individual communication acts to a focus on the quality of connections, particularly within dyadic communication. Through this relational perspective, the article explores how reciprocity and listening can serve as remedies to destructive polarization, fostering high-quality connections between citizens online. Reciprocity and listening are discussed as communicative mechanisms that should be nurtured as part of depolarization strategies. Finally, the article offers insights into what platform providers and community managers can learn from this theoretical exercise to promote democratic discourse online.